Protocolo de atendimento do cirurgião dentista no tratamento dos distúrbios do sono: ronco primário e síndrome da apnéia e hipopnéia obstrutiva do sono - Schiavoni, João Rodolpho [UNESP] (2014)
The dentist surgeon has a large work field supported by the scientific literature on sleep treatment disorders: primary snoring and apnea of mild to moderate intensity. However, these treatments are broadening. In this way, a treatment protocol should be followed in a way that the final result has the expected success. Not explored in a deep way, the dental society has, in lately years, improved this treatment modality and currently there are heaps of intra-oral devices that are efficient for both primary snoring to obstructive apnea and hypopnea. This kind of treatment has increased in a demand according to the evolution of the area of medicine focused on sleep. As a result it is possible to identify a variety of systemic diseases that have a major etiological main factor or sleep disorders, especially sleep apnea such as obesity, high blood pressure and even heart complications. Different from the continuous pressure devices for the apnea treatment, the intra-oral devices can be easily adapted by the patient, in addition it is portable and has a low cost. Moreover, it is necessary that the dentist surgeon was submitted into a training so that this type of work can be accurately done. This thesis has a literature review and a clinical case description to explain the treatment protocol that dental professionals should follow to obtain an optimised performance of intra-oral devices for treatment of these disorders